Severe Strongyloidiasis in Solid Organ Transplant Recipients: Should We Preventively Treat the Recipient, the Donor, or Both? - Eperon, Gilles (Am J Trop Med Hyg, 2018)
Strongyloidiasis is caused by a soil-transmitted helminth that is endemic in tropical and subtropical countries. The parasite can complete its life cycle without leaving the host, allowing autoinfection and persistence. The risk of infection in travelers is low, but the disease may become lethal following immunosuppression. In case of solid organ transplantation, the risk of donor transmission has been suspected for several years. However, the management of live donors in this context has only recently been considered, and no guidelines exist for the management of deceased donors. To highlight the complexity of diagnosing, treating, and preventing strongyloidiasis donor transmission, we describe a case of possible transmission of severe strongyloidiasis to a kidney transplant recipient with limited travel history. Taking into account the difficulty of diagnosing chronic strongyloidiasis infection and the increase in travel and immunosuppressive treatments, we recommend pragmatic management guidelines to limit the risks of infection.